Effect of yoga, meditation or body awareness on sports performance and attention in futsal players - Cascante Rusenhack, Marcio Maciel (2017)
Purpose: To determine the chronic effect of yoga, meditation or body awareness practice produces significant improvements in attention and sports performance in futsal players. A second aim was to determine the association between attention and sports performance. Methods: Thirty subjects (15 men, 15 women) were randomly assigned to four groups: Meditation (MG) (n = 8, mean age = 20.8 ± 2.4 yr.), Yoga (YG) (n = 8, mean age = 21.2 ± 1.6 yr.), Body awareness (BA) (n = 7, mean age = 20.5 ± 1.4 yr.), and Control Group (CG) (n = 7, mean age = 21.0 ± 2.3 yr.). Before (pre) and after (post) nine yoga, meditation or body awareness sessions, the subjects were measured on attention with the Stroop Test, and on sports performance with the Loughborough soccer passing test. Results: There was no significant interaction in attention and sport performance (p > 0.05). There were significant main effects in measurement (pre- to -post) on attention (Pre = 51.7 ± 5.7 vs. Post = 54.6 ± 4.5 hits, p < 0.05), and for sport performance (Pre = 65.2 ± 5.7 vs. Post = 63.6 ± 5.1-s, p < 0.05). No significant correlations were found between the change in attention scores and sport performance in experimental groups MG (r = 0.62), YG (r = 0.20), BA (r = 0.16), and CG (r = 0.20) (p > 0.05). Conclusions: Meditation, yoga and body awareness exercises do not influence attention or sport performance in futsal players.